Potent antiviral activity of novel multi-substituted 4-anilinoquin(az)olines. Issue 16 (15th August 2020) - Saul, Sirle; Pu, Szu-Yuan; Zuercher, William J.; Einav, Shirit; Asquith, Christopher R.M.
Graphical abstract: Abstract: Screening a series of 4-anilinoquinolines and 4-anilinoquinazolines enabled identification of potent novel inhibitors of dengue virus (DENV). Preparation of focused 4-anilinoquinoline/quinazoline scaffold arrays led to the identification of a series of high potency 6-substituted bromine and iodine derivatives. The most potent compound 6-iodo-4-((3, 4, 5-trimethoxyphenyl)amino)quinoline-3-carbonitrile (47 ) inhibited DENV infection with an EC50  = 79 nM. Crucially, these compounds showed very limited toxicity with CC50 values >10 µM in almost all cases. This new promising series provides an anchor point for further development to optimize compound properties.